2006
DOI: 10.1063/1.2202100
|View full text |Cite
|
Sign up to set email alerts
|

Observation of one-electron charge in an enhancement-mode InAs single-electron transistor at 4.2K

Abstract: We propose and demonstrate experimentally a novel design of single-electron quantum dots. The structure consists of a narrow band gap quantum well that can undergo a transition from the hole accumulation regime to the electron inversion regime in a single-top-gate transistor configuration. We have observed large size quantization and Coulomb charging energies over 10meV. This quantum dot design can be especially important for scalable quantum computing.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…If we model the QD as a disc with a radius r, the obtained capacitance of our QD suggests an effective diameter of about 20 nm, consistent with our numerical simulation considering a miniature MOS capacitor [7].…”
supporting
confidence: 68%
“…If we model the QD as a disc with a radius r, the obtained capacitance of our QD suggests an effective diameter of about 20 nm, consistent with our numerical simulation considering a miniature MOS capacitor [7].…”
supporting
confidence: 68%
“…NCs are interesting because of their characteristics that can be purposefully controlled by varying their size, shape, composition, and structure. This feature makes it possible to create devices based on new physical principles and to improve the performance of existing semiconductor devices . A 2 B 6 semiconductor NCs are among the most actively studied NCs because of the potential of enhancing the performance of lasers, photodetectors, solar cells, etc. …”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the method of top-gates, which is very successfull for realizing tunable nanostructures in GaAs heterostructures, is not straight forward on InAs. It has been shown that QDs can be realized in planar InAs heterostructures [9]. High quality QDs have been realized on nanowires (NWs), either by using Schottky contacts on InP [10] and Si NWs [11], or by epitaxial growth of InP barriers along an InAs NW [12,13].…”
Section: Introductionmentioning
confidence: 99%